MANAJEMEN LABA DALAM PRESPEKTIF ISLAM - Yosy Arisandy (Fakultas Syariah UINFAS Bengkulu, 2015)
Profit Management in the Perspective of Islam. This research was conducted to find outthe Islamic perspective on the activities Profit Management in the company's financial reporting. Thisstudy is an extension of previous research by Muhammad Faisol (2013) with some modifications. Thisresearch was done by using literature study between previous research on profit management inrelation to fraud or manipulation in comparison with literature about the rules of making a profit /earnings in accordance with Islamic law in the business. Earnings/profit management is allowed inaccordance with the rules of Generally Accepted Accouting Principles (GAAP). However, in view ofthe Islamic Sharia patterns used and the purpose of earnings management practices, it is not inaccordance with Islamic law in relation to the business a clear, honest, blessing and blessing.